2006
DOI: 10.1152/ajplung.00302.2005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulmonary arterial endothelial cells on quinone redox status: effect of hyperoxia-induced NAD(P)H:quinone oxidoreductase 1

Abstract: The objective of this study was to examine the impact of chronic hyperoxic exposure (95% O2 for 48 h) on intact bovine pulmonary arterial endothelial cell redox metabolism of 2,3,5,6-tetramethyl-1,4-benzoquinone (duroquinone, DQ). DQ or durohydroquinone (DQH2) was added to normoxic or hyperoxia-exposed cells in air-saturated medium, and the medium DQ concentrations were measured over 30 min. DQ disappeared from the medium when DQ was added and appeared in the medium when DQH2 was added, such that after approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 64 publications
7
41
0
Order By: Relevance
“…Thus the sensitivity of complex I activity in the present study is not that surprising, given previous reports of hyperoxic effects on various lung tissue and lung endothelial and epithelial cell mitochondrial functions, including complex I activity (4,7,11,14,41,46,53). We previously observed a hyperoxia-induced depression of complex I activity in the rat lung and bovine pulmonary arterial endothelial cells in culture (4,38). Functional or temporal relationships, if any, of the changes in complex I activity in hyperoxic lung injury on survival times in different mouse strains remain to be seen.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus the sensitivity of complex I activity in the present study is not that surprising, given previous reports of hyperoxic effects on various lung tissue and lung endothelial and epithelial cell mitochondrial functions, including complex I activity (4,7,11,14,41,46,53). We previously observed a hyperoxia-induced depression of complex I activity in the rat lung and bovine pulmonary arterial endothelial cells in culture (4,38). Functional or temporal relationships, if any, of the changes in complex I activity in hyperoxic lung injury on survival times in different mouse strains remain to be seen.…”
Section: Discussionsupporting
confidence: 79%
“…Hyperoxia was selected because it is a common model of acute lung injury and oxidative stress. Furthermore, our previous studies demonstrate that complex I activity and other mitochondrial functions are affected in rat lung exposed to hyperoxia (85% O 2 for 48 h) and in pulmonary arterial endothelial cells in culture (95% O 2 for 48 h) (4,27,38,39). We also evaluated the impact of the hyperoxic exposure on lung NQO1 activity because of the possibility that NQO1 induction could result in competition between NQO1 and complex I for CoQ 1 reduction.…”
Section: And Nqo1mentioning
confidence: 99%
“…It should be emphasized that the effect of hyperoxic exposure on pulmonary endothelial mitochondria would not have been revealed by measuring only the resting ⌬ m or using only a single commonly used CCCP concentration (5 M) to depolarize the mitochondria. Various indications of mitochondrial dysfunction have been reported by us and others in hyperoxiaexposed rat lung, pulmonary endothelial cells in culture, and other cell types (2,3,5,7,8,36,37,51,57). In this context, the present observations are consistent with a hyperoxia-induced mitochondrial deficiency.…”
Section: Discussionmentioning
confidence: 73%
“…Bovine pulmonary arterial endothelial cells were isolated from segments of calf pulmonary artery obtained from a local slaughterhouse and cultured to confluence on gelatincoated (2% vol/wt) Biosilon (polystyrene) microcarrier beads (230 m mean diameter, 160 cm 2 /ml beads), as previously described (12,41). The control cells were grown in room air; hyperoxia-exposed cells were subjected to 95% O 2-5% CO2 for 48 h, as previously described (36,37).…”
mentioning
confidence: 99%
“…Earlier studies also revealed that DQ behaves as an NQO1 probe in intact bovine pulmonary endothelial cells in culture (12,27). In the cell culture studies, DQ was added to the cell culture medium surrounding the cells, and the appearance of DQH 2 in the medium was measured.…”
Section: Discussionmentioning
confidence: 92%